Physicochemical properties and microbial community structure of the rhizosphere soil of Cymbidium tracyanum - Xie, Wenwen; Tang, Ying; Li, Haiming; Dang, Mingyu; Ci, Jianuo; Zheng, Min; Zhang, Erhao; Wang, Zhongbin (Frontiers in Microbiology, 2025)
To investigate the compositional characteristics of microbial communities in the rhizosphere soil of Cymbidium tracyanum (C. tracyanum) across different production regions in Tibet, as well as the correlation between these microorganisms and soil physicochemical factors, we analyzed soil microbial community composition in Bayi District, Chayu County, and Mêdog County in Linzhi City, Tibet, using Illumina MiSeq high-throughput sequencing technology. The results indicate that 7,467 bacterial operational taxonomic units (OTUs) and 2,866 fungal OTUs were identified in the rhizosphere soil of C. tracyanum. Significant differences were observed in the structural composition of bacterial and fungal communities across the different regions. The dominant bacterial phyla in the rhizosphere soil included Proteobacteria, Acidobacteria, Planctomycetota, and Firmicutes, while Ascomycota and Basidiomycota were the predominant fungal phyla. Additionally, variations in the physicochemical properties of the rhizosphere soil were observed among the different regions. Core microbiota analysis identified 214 core bacterial genera and 79 core fungal genera in the rhizosphere soil of C. tracyanum in Tibet. Correlation analysis revealed that changes in the core microbial community were associated with soil physicochemical factors to varying degrees, with total phosphorus and available phosphorus emerging as key factors influencing microbial diversity in the rhizosphere soil. In summary, the composition and diversity of bacterial and fungal communities in the rhizosphere soil of C. tracyanum varied across different production regions, and shifts in microbial community structure were closely linked to soil physicochemical factors.